Effect Of Pumpkin On The Sensory Quality Of Rice Noodles - Berliana Putri Nopalyu; Faridah Anni; Rahmi Holinesti; Sari Mustika (Universitas Negeri Padang, 2025)
Pumpkin (Cucurbita moschata) is a locally abundant commodity, yet its utilization remains limited to traditional dishes. Its high content of β-carotene, dietary fiber, and vitamins A and C makes pumpkin a potential functional food ingredient. To increase its added value and consumption, pumpkin was processed into puree and used to replace water in making rice flour noodles. Noodles were selected because of their popularity across Indonesia, while rice flour is naturally gluten-free and therefore safe for people with celiac disease. This study employed a true experimental design using a Completely Randomized Design (CRD) consisting of four treatments (0 mL, 160 mL, 180 mL and 200 mL pumpkin purée) with three replications. Sensory evaluation was conducted by 30 untrained panelists who were students of the Family Welfare Education Study Program, Universitas Negeri Padang. Data were analyzed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test if F > F. Results showed that the addition of pumpkin purée had a significant effect on noodle colour (bright yellow) and aroma (distinct pumpkin odour), but no significant effect on texture (chewiness) or taste (savouriness). The overall best treatment, based on the highest total hedonic acceptance score, was the noodle prepared with 200 mL (X₃) of pumpkin purée.